The many faces of periapical inflammation. Issue 9 (September 2020) - Boeddinghaus, R.; Whyte, A.
Abstract : Dental periapical inflammation is common and can present with a wide variety of symptoms and signs. These include jaw pain and local soft-tissue inflammation, which may be obviously dental in origin; however, the presentation may also be with a painless mass or draining cutaneous sinus, with facial or ear pain or with symptoms of sinusitis, when the dental cause is not clinically obvious. Radiologists are often the first to recognise the dental source of symptoms in these cases. This recognition requires an awareness of the varied manifestations of periapical sepsis and careful systematic review of the teeth and jaws. The causative periapical lesion may be small and subtle, and there is not always a macroscopic defect in the cortical bone between the lesion and surrounding soft-tissue inflammation. The origin of the referral and the initial imaging technique used can vary. Dental periapical inflammation can also be an incidental finding on imaging. In these cases, it should not be mistaken for more sinister pathology and its presence should be conveyed to the referrer so that appropriate dental treatment can be initiated: this is especially important in patients with malignancy in whom radiotherapy is planned. In cases of severe odontogenic soft-tissue sepsis, a review of the airway and major blood vessels is important. We present cases to illustrate the wide range of clinical and radiological manifestations of periapical inflammatory pathology.